Party Competition, Party Polarization, and the Changing Demand for Lobbying in the American States. (March 2015) - Gray, Virginia; Cluverius, John; Harden, Jeffrey J.; Shor, Boris; Lowery, David
Interest system density influences internal dynamics within interest organizations, how they lobby, and policy conditions. But how do political conditions influence interest system density? How does politics create demand for interest representation? We examine these questions by assessing how legislative party competition and ideological distance between parties in state legislatures affect the number of lobby groups. After stating our theoretical expectations, we examine 1997 and 2007 data on legislative competition and party polarization to assess their influence on system density. We find mixed results: Whereas politics slightly influenced the structuring of nonprofit interest communities, they seem to have not affected the structuring of for-profit interest communities or interest communities as a whole.